Empowering Teacher of Religious Education in Multicultural Society - Muslih, M (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
This paper revealed the result of research regarding the position of teacher, focusing on the importance of empowering teacher of religious education in multicultural society, such as Indonesia. Methodologically, it is a qualitative undertaking of literary research. Employing the technique of content analysis this study scrutinized features of multicultural society, an exemplary profile of teacher of religious education, as well as how to empower this kind of teacher in order to fit in with a diverse society. The findings of this research are, multicultural society can be understood as a society which consists of several cultural communities with their overlapping but the distinct conception of the world, a system of meaning, values, forms of social organizations, histories, customs, and practices. The idealized profile of teacher of religious education is a type of teacher who meets the certain qualifications prescribed by Islamic teachings and guided by the law and regulation in Indonesia, in particular.Â Teacher of religious education has a very important role in preparing students to be good citizens in a multicultural society. Therefore the teacher of religious education must have an awareness that he or she is part of a multicultural society. The teacher should be empowered to instill in his or her students an inclusive religious understanding to make them tolerant and respectful of other people of different cultures and religions, which is essential in order to strengthen harmony and national unity.Makalah ini mengungkapkan hasil penelitian mengenai posisi guru, berfokus pada pentingnya memberdayakan guru pendidikan agama dalam masyarakat multikultural, seperti Indonesia. Secara metodologis, ini adalah sebuah upaya penelitian literatur (kualitatif). Dengan menggunakan teknik content analysis penelitian ini menganalisa featuresÂ masyarakat multikultural, profil ideal guru pendidikan agama, serta bagaimana memberdayakan guru semacam ini agar sesuai dengan kondisi masyarakat yang beraneka ragam. Temuan penelitian ini adalah, masyarakat multikultural dapat dipahami sebagai masyarakat yang terdiri dari beberapa komunitas budaya dengan konsepsi yang tumpang tindih tapi berbeda tentang dunia, sistem makna, nilai, bentuk organisasi sosial, sejarah, adat istiadat dan praktek.Â Profil ideal guru pendidikan agama adalah jenis guru yang memenuhi kualifikasi tertentu yang ditentukan oleh ajaran Islam dan dipandu oleh hukum dan peraturan di Indonesia, khususnya. Guru pendidikan agama memiliki peran yang sangat penting dalam mempersiapkan murid-murid untuk menjadi warga negara yang baik di tengah masyarakat multikulural. Oleh karena itu guru pendidikan agama harus memiliki kesadaran bahwa ia adalah bagian dari masyarakat multikultural. Guru tersebut harus diberdayakan untuk menanamkan dalam diri muridnya pemahaman keagamaan yang inklusif untuk membuat mereka toleran dan hormat pada orang lain yang berbeda kultur dan agama, ini penting dilakukan agar dapat mempekuat harmoni dan kesatuan nasional.